New Recombination Methods for Sinorhizobium meliloti Genetics - House, Brent L. (American Society for Microbiology, 2004)
The availability of bacterial genome sequences has created a need for improved methods for sequence-based functional analysis to facilitate moving from annotated DNA sequence to genetic materials for analyzing the roles that postulated genes play in bacterial phenotypes. A powerful cloning method that uses lambda integrase recombination to clone and manipulate DNA sequences has been adapted for use with the gram-negative α-proteobacterium Sinorhizobium meliloti in two ways that increase the utility of the system. Adding plasmid oriT sequences to a set of vehicles allows the plasmids to be transferred to S. meliloti by conjugation and also allows cloned genes to be recombined from one plasmid to another in vivo by a pentaparental mating protocol, saving considerable time and expense. In addition, vehicles that contain yeast Flp recombinase target recombination sequences allow the construction of deletion mutations where the end points of the deletions are located at the ends of the cloned genes. Several deletions were constructed in a cluster of 60 genes on the symbiotic plasmid (pSymA) of S. meliloti, predicted to code for a denitrification pathway. The mutations do not affect the ability of the bacteria to form nitrogen-fixing nodules on Medicago sativa (alfalfa) roots.